Integration of Multi-Source Archival Data for 3D Reconstruction of Non-Existent Historical Buildings - Beata Calka; Paulina Jaczewska; Justyna Slowik (Applied Sciences)
The city of Warsaw, Poland, has endured significant damage throughout its history, particularly during World War II. The city was bombed in September 1939, and many buildings were blown up following the Warsaw Ghetto Uprising in May 1943. The Warsaw Uprising in August and September 1944 led to further destruction from artillery bombardments and fires. Even after the surrender and civilian evacuation in October 1944, additional demolitions occurred, leaving almost 90% of Warsaw in ruins. Despite ongoing efforts to rebuild the city, many landmarks could not be fully reconstructed. However, invaluable historical archives preserve remnants of Warsaw’s rich history. To reconstruct 3D models of pre-war buildings in Warsaw, a methodology was developed that integrates cartographic materials, spatial data, and results from tachymetric measurements. Historical maps, terrestrial and aerial photographs, and architectural blueprints from the National Archives in Warsaw were used to propose three distinct approaches to 3D modeling. Notable structures such as the Grand Synagogue, the Kamienica Theater building, and the Tłomackie buildings were selected for 3D modeling. These buildings either were destroyed or endured significant damage during the war. The 3D modeling process involved meticulous processing and calibrating of historical photographs alongside tachymetric surveying for accurate measurements. The proposed methodology showcases the feasibility of recreating 3D renderings of historical edifices, even those lost to time, utilizing archival cartographic data and spatial information from diverse sources. By leveraging cartographic heritage with digital advancements, a unique perspective on Warsaw’s narrative can be gained, enriching the understanding of its past for both residents and professionals such as historians, archivists, and cartographers.